DEVELOPMENT OF INTEGRATED IPA HANDOUTS ON ENVIRONMENTAL POLLUTION MATERIAL IN CLASS VII SMPN 4 SORONG - Yannika Nidiasari; Endra Putra Raharja; Nur Haeni Daeng Cahaya (Universitas Negeri Makassar, 2024)
This study discusses the development of Integrated Science Handout on Environmental Pollution Material for VII grade students of SMPN 4 Kota Sorong. This research conveys teaching materials (valid, practical and effective) in order to create handouts that are worth using. Type of research is Research and Development with the 4-D development model. The subjects of this research include 1 material expert, 1 media expert, and VII grade students of SMPN 4 Kota Sorong. The instruments used include feasibility questionnaires by material and media experts, as well as student response questionnaires to the use and posttest and pretest trials to assess effect of using handouts. The results of this test are: (1) Got an assessment value of 81 % on handouts by material experts in the classification of